1994
DOI: 10.1021/bi00199a022
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Induces Interdigitated Domains in Unilamellar Phosphatidylcholine Bilayers

Abstract: Using the atomic force microscope (AFM) in situ, we have demonstrated that acyl chain interdigitation can be induced reversibly by alcohol in supported unilamellar phospholipid bilayers. At alcohol concentrations considerably lower than the critical values determined by other experimental techniques, it was found that interdigitated domains can be induced and these domains were stable over a long period of time. The mechanism of such domain formation remains to be elucidated. This work also serves as an exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
167
2
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 20 publications
24
167
2
1
Order By: Relevance
“…Mou et al 43 were able to induce defects into dipalmitoylphosphatidylcholine (DPPC) bilayers by fast (200 Hz) scanning at high (30 nN) forces. We could not induce such defects into our EPC/cholesterol bilayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mou et al 43 were able to induce defects into dipalmitoylphosphatidylcholine (DPPC) bilayers by fast (200 Hz) scanning at high (30 nN) forces. We could not induce such defects into our EPC/cholesterol bilayers.…”
Section: Resultsmentioning
confidence: 99%
“…Bilayers formed from vesicles that spontaneously spread on solid substrates have been described before. 42, 43 We used the following protocol: the AFM head equipped with a standard fluid cell (Digital Instruments) was mounted on freshly cleaved mica (Plano, Wetzlar, Germany) and the fluid cell was flushed with buffer 1. After 15-60 min, a 20 µm image of the mica surface was taken to ensure that it was clean.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, through the use of atomic force microscopy (AFM), the nm-scale structures of phospholipid films have been investigated [11,12,13,14,20,21]. While these studies revealed the lateral structures of these films (e.g., domain formation, ripple structure), most observed only one or a few layers of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] These lipid layers have also been useful for the biomedical research of cell recognition, membrane-mediated catalysis, anesthetic effect, and antimicrobial peptide activity. [11][12][13][14][15] The actions of the phospholipases have also been investigated using these bilayers, to study the effect of the enzymes on the wetting properties and the configuration of the bilayers, as well as the activity of the enzymes.…”
Section: 6mentioning
confidence: 99%